EVALUATION OF SCHOOL EXTRACURRICULAR PROGRAMS TO IMPROVE LEADERSHIP AND STUDY MOTIVATION AT SDN JATISAMPURNA IX BEKASI IN 2019 - Adi Yuda PERMANA (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2020)
This research aims to see the level of success in achieving the goals set in the Evaluation of the Scout Extracurricular Program. This research is a qualitative descriptive study using the Context, Input, Process, Product (CIPP) evaluation model to determine the level of success in achieving the goals set in the Evaluation of the Scout Extracurricular Program at SDN Jatisampurna IX Bekasi. The subjects of this study were the Principal, Guidance Scouts, and students. Data collection techniques with the study of documentation, observation and interviews. Data analysis uses an interactive analysis model that is data collection, data reduction, data presentation and drawing conclusions. Context Component, all policies that have been established for the implementation of the Scout Extracurricular program in the Context component are eligible. Input Components, all the standard criteria that have been set for the implementation of the Scout Extracurricular program on the input components are good but there are components that have not been fulfilled with additional supervisors to support the activities of Scout Extracurricular programs in a better direction. The Process Component, there are some standards that are not implemented such as not holding a group discussion, the teacher/subject has not fully implemented the assistance properly, there are still teachers who do not accompany students, provide direction, or monitor. Product Component, the standard that has been set based on the product component is good but the optimization occurs in the community participation as a supervisor doesn’t go well.